A CASE OF HYPERCALCEMIA CRISIS IN PREGNANCY DUE TO GIANT PARATHYROID ADENOMA - Sy, Eng; Tan, Florence HS (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypercalcemia in pregnancy affects 0.03% of reproductive women. Complications are directly related to maternal calcium level and include maternal nephrolithiasis, kidney injury, pancreatitis, pre-eclampsia and fetal loss. Primary hyperparathyroidism accounts for >90% of cases. CASE We report a 41-year-old female who presented at 4 weeks of gestation with a 1-week history of polyuria and 3-day history of epigastric pain. Laboratory investigations showed the following: severe hypercalcemia with corrected serum calcium of 5.04 mmol/L, low serum phosphorous at 0.88 mmol/L, elevated intact PTH at 45.4 (NR:1.6-6.0 pmol/L), acute kidney injury with serum creatinine of 221 umol/L, and pancreatitis with serum amylase of 368 (NR: 62-106 u/L). Electrocardiogram showed Osborn waves. Kidney ultrasound showed bilateral renal medullary nephrocalcinosis with nephrolithiasis. Neck ultrasound revealed a 2.8x2.9x5.1 cm well defined solid lesion postero-inferior to the right thyroid lobe suggestive of parathyroid tumour. Oral cinacalcet and subcutaneous calcitonin were initiated when saline diuresis failed to lower her calcium below 4 mmol/L. Calcitonin was discontinued after 2 days due to intolerability. At the 5th hospital day, serum calcium and creatinine levels decreased to 2.77 mmol/L and 103 umol/L, respectively, with high volume intravenous saline and cinacalcet. A multidisciplinary discussion was done and the plan was to continue oral cinacalcet and parathyroidectomy at the second trimester. Unfortunately, serial beta-hCG showed decreasing levels and transvaginal ultrasound confirmed fetal nonviability. Left inferior parathyroidectomy was then performed on the same setting at day 7 of presentation. Histopathologic examination reported giant parathyroid adenoma weighing 23 g. Her calcium level normalised and she remained normocalcemic at follow-up 5 months post-surgery. CONCLUSION Our case highlights the management challenges for hypercalcemia in pregnancy due to safety concerns on standard pharmacotherapy and surgery. Acute management of severe hypercalcemia in pregnancy requires timely multidisciplinary decisions to achieve the best outcome and minimise morbidity and mortality.